Relativistic Stark energies of hydrogen-like ions - Maltsev, I. A; Tumakov, D. A; Popov, R. V; Shabaev, V. M (2023)
The relativistic energies and widths of hydrogen-like ions exposed to the uniform electric field are calculated. The calculations are performed for the ground and lowest excited states using the complex scaling technique in combination with a finite-basis method. The obtained results are compared with the non-relativistic values. The role of relativistic effects is investigated.